A FREUDIAN PSYCHOLOGICAL ISSUE OF WOMEN CHARACTERS IN DAPHNE DU MAURIERÃ¢â¬â¢S NOVEL REBECCA - Margawati, Prayudias (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2010)
A literary work can be appreciated through some ways. A psychological literary approach is made within the work. A creative process model is discussed in this subject since a work of literature often be considered as writerÃ¢â¬â¢s creation which is sometimes related to psychological symptoms such as obsession, contemplation, sublime and some neurosis. A determination of Sigmund Freud theory mostly occurs in psychological approach applied to literature. By identifying human unconsciousness, it can be found through Du MaurierÃ¢â¬â¢s novel, Rebecca, that Id, Ego and Super Ego as personality theory appeared to be psychological aspects in fictional women characters. It reflects how those characters react to conflicts through the story. Keyword: psychology, unconsciousness, personality theory, women characters